2012
DOI: 10.1093/jnci/djs188
|View full text |Cite
|
Sign up to set email alerts
|

Staging and Functional Characterization of Pheochromocytoma and Paraganglioma by 18F-Fluorodeoxyglucose (18F-FDG) Positron Emission Tomography

Abstract: Compared with (123)I-MIBG SPECT and CT/MRI, both considered gold standards for PPGL imaging, metastases were better detected by (18)F-FDG PET. (18)F-FDG PET provides a high specificity in patients with a biochemically established diagnosis of PPGL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
142
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 245 publications
(157 citation statements)
references
References 29 publications
8
142
1
6
Order By: Relevance
“…However, the utility of 123 I-MIBG needs further evaluation. 18 F-FDG is currently the radiopharmaceutical of choice in metastatic PPGL (22)(23)(24) and has good accuracy, especially in patients with more dedifferentiated tumors and underlying SDHB mutations (20,25). These tumors show upregulated expression of glucose transporters as well as an upregulation of hexokinase, which explains the high 18 F-FDG uptake in tumors with SDH subunit A-D (collectively SDHx) deficiency (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…However, the utility of 123 I-MIBG needs further evaluation. 18 F-FDG is currently the radiopharmaceutical of choice in metastatic PPGL (22)(23)(24) and has good accuracy, especially in patients with more dedifferentiated tumors and underlying SDHB mutations (20,25). These tumors show upregulated expression of glucose transporters as well as an upregulation of hexokinase, which explains the high 18 F-FDG uptake in tumors with SDH subunit A-D (collectively SDHx) deficiency (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Kaji et al showed that 18 F-fluorodihydroxyphenylalanine PET is superior to 123 I-MIBG scintigraphy in the context of von HippelLindau syndrome (26). We have previously shown that 18 F-FDG PET can distinguish between PPGLs with different underlying genotypes, and sensitivity of 18 F-FDG PET is higher in SDHB/Drelated PPGLs than non-SDHB/D-related metastatic PPGLs (92% vs. 37%) (38). The sensitivity of 123 I-MIBG scintigraphy appears to be lower in VHL-and SDHB-related PPGLs (22,25,26).…”
Section: Discussionmentioning
confidence: 93%
“…The 18 F-FDG uptake reflects glucose uptake and behaves as an analog of glucose, its distribution closely follows that of glucose-metabolizing cells and organs but with some differences. The 18 F-FDG enters cells by membrane Glucose Transporters (GLUTs) then undergoes phosphorylation by hexokinase to form 18 FDG-6-phosphate [5,6], unlike glucose, this undergoes further enzymatic reactions and is effectively trapped into the cell. Increased uptake of 18 F-FDG is not specific to paragangliomas, however, most paragangliomas are avid for F 18 FDG despite their relative indolence [5,6].…”
Section: Discussionmentioning
confidence: 99%